Effect of shading and ethephon on the anthocyanin composition of ‘Crimson seedless’ (Vitis vinifera L.) - Human, Michael Adriaan (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScAgric (Viticulture and Oenology)--University of Stellenbosch, 2010.